KOMUNIKASI KEPEMIMPINAN JOGER PABRIK KATA-KATA DALAM MEMBANGUN MOTIVASI KERJA - Nurbaiti, Ella Dia; Alit Suryawati, I Gusti Agung; Purnawan, Ni Luh Ramaswati (E-Jurnal Medium, 2019)
ABSTRACT The success of the organization in achieving the goals it wants to achieve depends on its leadership. To realize the goals of the organization the leader must communicate effectively with staff . Joger Kata-Kata Factory has been established only 37 and has more than 300 members of the Joger afamily. The purposei of this astudy awas to afind oout how Joger Factory Kata-Word leadership communication in building work motivation from members of the Joger family. This research is a qualitative research - descriptive by using interview data collection techniques, observation and documentation studies and informant determination techniques usingapurposive sampling itechnique. The iresults of ithis istudy show that leaders in building work motivation from members of the Joger Word Factory family by implementing effective leadership communication in accordance with the concepts proposed by Barret and have fulfilled the needs of Joger family members according to maslow's hierarchy of needs theories. Keywords: Communication, Leadership, Work Motivation, Joger Pabrik Kata Kata.